Social preferences under risk: Minimizing collective risk vs. reducing ex-post inequality - Alexia Gaudeul (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
We refine the understanding of individual preferences across social lotteries, whereby the payoffs of a pair of subjects are exposed to random shocks. We find that aggregate behavior is ex-post and ex-ante inequality averse, but also that there is a wide variety of individual preferences and that the majority of subjects are indifferent to social concerns under risk. Furthermore, we determine whether subjects are averse to collective risk - the variability in the sum of payoffs of the pair. We do so by varying the presentation of payoffs. They are shown side by side in one treatment and added-up in the other. The first presentation draws attention to inequality in payoffs, the second to collective risk. We find that subjects dislike lotteries that lead to ex-post unequal distributions of payoffs in both cases and that emphasizing collective risk changes choice only marginally and not significantly, though in the direction of collective risk reduction. We conclude that ex-post inequality aversion is the primary concern in the evaluation of social lotteries while collective risk is only of secondary interest.
Keywords: C91; D63; D81; 330; Altruism; Collective Risk; Experimental Economics; Fairness; Inequality; Risk; Social Lotteries; Social Preferences